The impact of Covid-19 on ECG: A case-control study - Kaya, Bedri Caner; Kaya, Berna (Journal of Surgery and Medicine, 2021)
Background/Aim: Coronavirus Disease 2019 (Covid-19) is a pandemic with fatal effects on the respiratory and cardiovascular systems. Early recognition of complications in the cardiovascular system in Covid-19 disease will guide our treatment management. Therefore, we aimed to examine the changes that occurred in the ECGs of patients with a Covid-19 infection in the last year who were admitted with palpitations. Methods: Patients who presented to the Cardiology and Internal Medicine outpatient clinics with a complaint of palpitation between June 2021 and July 2021 and who had a Covid-19 infection in the last year were included in this study. A total of 212 patients with a history of Covid-19 and a control group of 185 people without Covid-19 history and cardiac diseases were compared. At admission, QTc, Tp-e interval, frontal QRS-T angle, and fragmented QRS were evaluated on Electrocardiography (ECG). Results: Among patients with a history of Covid-19 disease, there were 127 (59.91%) males and 85 (40.09%) females. Within the control group, 71 (38.38%) were males and 114 (61.62%) were females. In patients who had a Covid-19 infection, QTc (OR: 1.071, 95% CI: 1.042-1.100, P<0.001), frontal QRS-T angle (OR: 1.054, 95% CI: 1.015-1.095, P=0.007), and Tp-e interval (OR: 1.253, 95% CI: 1.140-1.377, P<0.001) were significantly increased. The difference in fragmented QRS (P=0.230) was not significant in logistic regression analysis. Conclusion: We found increased QTc, Tp-e, and fQRS-T angles in patients who had Covid-19 disease, all of which indicate ventricular repolarization abnormality. Therefore, those with Covid-19 infection should be followed up for malignant arrhythmias.